Curcumin Improves the Regulation of Ovarian Folliculogenesis in Culture Media with Peritoneal Fluid from Infertile Women with Endometriosis - Hendy Hendarto1, M Yohannes Ardianta Widyanugraha1, Widjiati2, Soehartono Darmosoekarto1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background : Peritoneal fluid (PF) from infertile women with endometriosis contains a variety of inflammatory mediators that may interfere with folliculogenesis. The aim of the study was to evaluate effects of curcumin on the regulation of ovarian folliculogenesis by evaluating Growth Differentiation Factor (GDF)-9, Kit Ligand (KitL) and Tumor Necrosis Factor (TNF)? expressions in bovine cumulus oocyte complexes (COC)s cultured with PF from infertile women with endometriosis. Method: COCs were aspirated from antral follicles of bovine ovaries. PF was collected from infertile women with endometriosis undergoing laparoscopy for infertility evaluation. Curcumin, a strong antiinflammatory turmeric, was added in Tissue Culture Media (TCM)199 and PF from infertile women with endometriosis for culture media. Bovine COCs were cultured into 3 groups of media: 1) TCM199, 2) TCM199+PF from infertile women with endometriosis, and 3) TCM199+PF from infertile women with endometriosis+curcumin. GDF-9, KitL and TNF? expressions were examined using immunohistochemistry technique. Results: GDF-9 expression of bovine COCs cultured in PF from infertile women with endometriosis with curcumin addition (2.67±0.98) was found to increase compared to those cultured without curcumin (0.50±0.67) but reduced compared to the control. This result was similar to KitL expression of bovine COCs cultured with curcumin (2.67±1.23), in which it increased compared to those without curcumin (0.33±0.49) (p<0.05). A significant difference in TNF? expression was noted between groups with or without curcumin (p<0.05). Conclusion: In the culture of PF from infertile women with endometriosis, curcumin addition may improve the regulation of ovarian folliculogenesis through the decrease of inflammation factor.